Effect of Platelet-derived P-selectin on Neutrophil Recruitment in a Mouse Model of Sepsis-induced Acute Kidney Injury - Xiu-Hua Li; Yong-Bing Qian; Xiao-Xiao Meng; Rui-Lan Wang (Chinese Medical Journal, 2017)
Background: Acute kidney injury (AKI) is a severe disease in critically ill patients. Neutrophil infiltration into kidney was associated with the development of AKI, and P-selectin may be involved in the process of neutrophil recruitment in kidney. This study aimed to explore the potential effect of platelet-derived P-selectin on neutrophil recruitment in a mouse model of sepsis-induced AKI. Methods: A total of 30 C57BL/6 male mice were divided into five groups (n = 6 in each): sham group, sepsis group, anti-Ly6G group, anti-P-selectin group, and platelet depletion group. Sepsis was induced by cecal ligation and puncture. Serum creatinine concentration and platelet activity were measured by biochemical detector and flow cytometry, respectively. Histological and pathological features were analyzed using hematoxylin-eosin (H&E) and immunohistochemistry (IHC) staining, respectively. Myeloperoxidase (MPO) activity was detected with MPO assay. Unpaired t-test was used for data analysis. Results: Serum creatinine increased significantly in septic group compared to sham group (2.68 ± 0.27 mg/dl vs. 0.82 ± 0.19 mg/dl, t = 12.06, P = 0.0000) but attenuated in antibodies-treated animals compared to septic group (anti-Ly6G: 1.62 ± 0.30 mg/dl vs. 2.68 ± 0.27 mg/dl, t = 5.76, P = 0.0004; anti-P-selectin: 1.76 ± 0.31 mg/dl vs. 2.68 ± 0.27 mg/dl, t = 4.92, P = 0.0012; and platelet depletion: 1.93 ± 0.29 mg/dl vs. 2.68 ± 0.27 mg/dl, t = 4.14, P = 0.0032). Platelet amount significantly decreased compared to sham group (658.20 ± 60.64 × 109/L vs. 822.00 ± 48.60 × 109/L, t = 4.71, P = 0.0015) in septic mice, especially in platelet depletion group (240.80 ± 44.98 × 109/L vs. 822.00 ± 48.60 × 109/L, t = 19.63, P = 0.0000). P-selectin activity was significantly increased in septic group compared to sham group (16.54 ± 1.60% vs. 1.90 ± 0.29%, t = 15.64, P = 0.0000) but decreased significantly in platelet depletion group compared to septic group (3.62 ± 0.68% vs. 16.54 ± 1.60%, t = 12.89, P = 0.0002). IHC analysis shown that neutrophil infiltration increased in septic mice compared to sham group (36.67 ± 3.79% vs. 9.17 ± 1.61%, t = 11.58, P = 0.0003) and function-blocked groups (anti-Ly6G: 36.67 ± 3.79% vs. 15.33 ± 1.53%, t = 9.05, P = 0.0008; anti-P-selectin: 36.67 ± 3.79% vs. 21.33 ± 1.53%, t = 6.51, P = 0.0029; and platelet depletion: 36.67 ± 3.79% vs. 23.33 ± 3.06%, t = 4.75, P = 0.0090). MPO increased significantly in septic group compared to control (49.73 ± 1.83 ng/mg prot vs. 13.04 ± 2.16 ng/mg prot, t = 19.03, P = 0.0000) but decreased in function-blocked groups compared to septic group (anti-Ly6G: 26.52 ± 3.86 ng/mg prot vs. 49.73 ± 1.83 ng/mg prot, t = 9.59, P = 0.0000; anti-P-selectin: 33.06 ± 6.75 ng/mg prot vs. 49.73 ± 1.83 ng/mg prot, t = 4.85, P = 0.0013; and platelet depletion: 33.37 ± 2.25 ng/mg prot vs. 49.73 ± 1.83 ng/mg prot, t = 5.33, P = 0.0007). Conclusion: Platelets-derived P-selectin may be involved in the development of septic AKI through inducing neutrophil infiltration into kidney.